Rhythms of the Domestic Soundscape: Ethnomethodological Soundwalks for Phatic Technology Design - Baharin, Hanif; Rintel, Sean; Viller, Stephen (INTERACT 2013, Part IV, LNCS 8120, 2013)
The importance of the domestic soundscape as a context for technological interventions has received little attention in HCI research. In this paper, we discuss how an ethnomethodological soundwalk method facilitated design principles for a phatic technology probe for seniors living alone. Taking soundscape concepts as a starting point, we suggest that the soundwalk works much like a breaching experiment, changing the participant’s role in engaging with their soundscape from reactive automatic agent to proactive reflective agent. This enables participants to reveal their own systematic orderliness when accounting for everyday sounds. We find that sounds are accounted for in terms of people placed in narratives. As such, we argue that phatic technologies use new sounds and rhythms to augment the domestic soundscape to take advantage of people’s abilities to create social narratives from limited cues.